2016
DOI: 10.1051/shsconf/20162601025
|View full text |Cite
|
Sign up to set email alerts
|

Investigating of conceptions of learning biology with respect to gender, grade level and school type

Abstract: Abstract. The aim of this study was to describe the students' conceptions of learning biology (COLB) and investigate students' COLB with respect to gender, grade level and school type. COLB questionnaire was implemented in 1691 high school students. In general, this study recognized students preferred higher-level conceptions of learning (increasing knowledge, application, understanding and seeing in a new way) to lower-level conceptions (memorizing, preparing for exams and calculating and practicing). Based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Similar to the findings of previous studies in traditional science learning contexts Sadi & Cevik, 2016), the higher grade students in this study tended to possess more sophisticated conceptions of learning science by AR as extending learning content (extending) and creating interaction between learners and learning materials (interaction) than the lower grade students did. In addition to the positive conceptions, the higher grade students also showed an inclination to think negatively about learning science by AR (i.e., obstructing reading and diminishing imagination).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Similar to the findings of previous studies in traditional science learning contexts Sadi & Cevik, 2016), the higher grade students in this study tended to possess more sophisticated conceptions of learning science by AR as extending learning content (extending) and creating interaction between learners and learning materials (interaction) than the lower grade students did. In addition to the positive conceptions, the higher grade students also showed an inclination to think negatively about learning science by AR (i.e., obstructing reading and diminishing imagination).…”
Section: Discussionsupporting
confidence: 85%
“…Similar results were found in Sadi and Lee's study (2015), which reported that female students considered learning science with higher levels of conception than male students. However, some other studies with large sample sizes (e.g., Sadi & Cevik, 2016 with 1,691 high school students) did not find any interaction between students' gender and their conceptions of learning science. Grade level is another demographic variable included in the studies of students' conceptions of learning science.…”
Section: Demographic Variables and Conceptions Of Learning Sciencementioning
confidence: 71%
See 1 more Smart Citation
“…Scholars have delved into the factors influencing the acquisition of scientific knowledge and have established that students' conceptions of learning science (COLS) are impacted by variables such as grade level, school type, and teaching methodologies employed by educators (Sadi & Cevik, 2016). These conceptions of learning pertain to the beliefs and perceptions held by students about their learning experiences and their preferred approaches to learning (Liang & Tsai, 2010).…”
Section: Conceptions Of Learning Science In Technology-enhanced Envir...mentioning
confidence: 99%
“…Besides the influence of curriculum on students' conceptions of learning science, some factors were also found to significantly contribute to students' conceptions of learning science, particularly gender (e.g., Den Brok, Telli, Cakiroglu, Taconis & Tekkaya, 2010;Lonka & Lindblom-Ylänne, 1996;Sadi & Çevik, 2016) and the specific domain of science subjects (e.g., Buehl & Alexander, 2001;Lin, Liang & Tsai 2015;Sadi & Lee, 2017;Sadi, 2015;Tsai, 2006). In terms of the gender issue in cognitive and affective aspects of learning science, Severiens & Dam (1997), in their research of gender differences in learning styles, have pointed out that the differences in learning and learning outcomes are derived from the inequality in learning environments that may result from teachers' and society's stereotyping of gender.…”
Section: Introductionmentioning
confidence: 99%